2010
DOI: 10.1111/j.1746-1561.2010.00501.x
|View full text |Cite
|
Sign up to set email alerts
|

Student and Teacher Perceptions of School Climate: A Multilevel Exploration of Patterns of Discrepancy

Abstract: Teacher ratings were more sensitive to classroom-level factors, such as poor classroom management and proportion of students with disruptive behaviors, whereas student ratings were more influenced by school-level factors such as student mobility, student-teacher relationship, and principal turnover. The discrepancy in ratings of academic emphasis suggests that while all of the respondents may have shared objectively similar experiences, their perceptions of those experiences varied significantly. These results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
112
2
20

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 204 publications
(145 citation statements)
references
References 34 publications
11
112
2
20
Order By: Relevance
“…Previous studies revealed that gender has been shown to be related to learning environment perceptions [52] as well as to mathematics self-concept and interest [10,53]. Ditton [19], for example, showed that male students evaluate their mathematics teachers' performance more positively than their female classmates.…”
Section: Characteristics Of Instructional Quality Mathematics Self-comentioning
confidence: 99%
“…Previous studies revealed that gender has been shown to be related to learning environment perceptions [52] as well as to mathematics self-concept and interest [10,53]. Ditton [19], for example, showed that male students evaluate their mathematics teachers' performance more positively than their female classmates.…”
Section: Characteristics Of Instructional Quality Mathematics Self-comentioning
confidence: 99%
“…A surprising result, however, was that whereas in the initial analysis teachers' perceptions of student behavior, classroom climate and confidence in teaching methods were significant, their effect was not significant in the model shown in Figure 1. This focus on teachers' perceptions of classroom environment has been somewhat neglected in research on civic learning but has been explored in other school research (Mitchell, Bradshaw, & Leaf, 2010). Here it has been argued that teachers are more inclined to make global assessments of their classroom while students are more likely to make individual assessments.…”
Section: Discussionmentioning
confidence: 99%
“…a tanár vezetési stílusa, a rendbontó tanulók aránya az osztályban) az iskolai szinthez kapcsolódó változók (pl. az osztályok mé-rete, az iskola eredményességének mutatói, az iskola összetétele) befolyásolják erőtelje-sebben, miközben a tanárok klímaértékelését az osztálytermi tényezők határozzák meg (Mitchell, Bradshaw és Leaf, 2010). A kutatók kiemelik továbbá, hogy a klíma nem egy konkrét, mindenki által egyformán észlelt jelenség, hanem szubjektív, egyéni módon szerveződő konstruktum.…”
Section: Marshall 2004 Tanulók Tanárokunclassified